31 Development of a web-based screening tool 'CranioQ' to support the identification of children with craniofacial defects. (30th November 2020) - Abedin, Yasmin; Brinkmeyer, Andrew; Hughes, Sioban; Bassi, Daiana; Conner, Sue; Fu, Yun; Mohamedally, Dean; Molyneux, Gemma; Sebire, Neil J; Borghi, Alessandro; ONg, Juling
Abstract : Many babies develop an asymmetric or unusual head shape in the first few months of life called deformational plagiocephaly, which will usually resolve without intervention. However, in a small number of children, this abnormality will be very similar to the appearance of an underlying congenital craniofacial condition that requires further review by a craniofacial team. Identifying children that require further investigation, and specialist referral, can be difficult for community healthcare professionals. To improve diagnosis and time to surgical consult, we have developed a web-based screening tool. This project was initiated to investigate the possibility of deploying the GOSH Craniofacial Screening tool via a web portal, to allow community healthcare professionals to rapidly seek a second opinion from the specialist craniofacial team at GOSH. As part of a joint collaboration between GOSH and UCL computer science (CS) through the industry exchange network programme, a website was developed using Django with a PostgresSQL database and an Angular front-end. This tool relies on the co-operation of parents, community healthcare professionals and specialist craniofacial teams. The tool consists of a set of questions focussing on the child's health and development. The GP enters some basic medical information onto the website to generate a questionnaire, this is made available to parents for completion via a single use pass code. Once all of the information is submitted the specialist craniofacial team at GOSH are alerted to the new case requiring review. The team can comment on the case and request further investigations via the web tool, to ascertain if referral is required. The overall aim is to support community healthcare professionals detect craniofacial conditions, so that patients requiring specialist care receive attention rapidly. The tool has the potential to support early recognition and diagnosis of craniofacial conditions reducing the time to referral.